Feyzî-i Kefevî’s Ravżatü’l-ʻİbād textual analysis and transcribed text - Altuntaş, Resul. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
In this study, the main focus is Ravzatü’l-‘İbâd, which is a forty-hadith translation made by Haydar-zâde Feyzî-i Kefevî in the seventeenth century. It consists of the transcribed text of Ravzatü’l-‘İbâd, which was written in the classical mathnawi form and research on the forty hadiths genre in general. In the first chapter there is a brief examination about the historical process of the genre, including Arabic, Persian and Turkish literartures. Also this chapter discusses the author’s intentions, which affect directly the forms and contents of the works, through the comparision between Fuzûlî and Mustafa Âlî’s intentions that are stated in their works. The second chapter focuses on the stylistic and contextual analysis of the Ravzatü’l-‘İbâd and also consists of some information about the author Feyzî-i Kefevî and his other works. Moreover this chapter contains an examination on literary style and classical literature’s patterns of the Ravzatü’l-‘İbâd. It is claimed that regarding the use of language and the content, this work was written in order to be read in a group activity and there is no place for women as an audience. The third chapter consists of the transcribed text of Ravzatü’l-‘İbâd. Feyzî gives the Arabic versions of the 40 sahih hadiths with their Turkish translations and expounds on these hadiths with counsel (pend), story (hikâyet) and invocation (münâcât) parts. There are interesting examples of prophetic stories, anecdotes about saints and folktales. The most distinctive part of this sudy is that it examines the forty hadiths genre as a literary work by subjecting a stylistic and contextual examination.